1979
DOI: 10.1037/h0077603
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine depletion in mice upon reexposure to stress: Mediation of the escape deficits produced by inescapable shock.

Abstract: Immediately following exposure to 60 inescapable shocks, Swiss-Webster mice had significantly reduced hypothalamic norepinephrine (NE). Within 24 hr NE levels returned to control values. Reexposure to as few as 10 shocks 24 hr after initial stress exposure resulted in a significant decline of hypothalamic NE. Moreover, at this interval after inescapable shock, escape performance was severely disrupted, with a large proportion of mice exhibiting numerous failures to escape shock. Increasing brain dopamine (DA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(52 citation statements)
references
References 21 publications
2
48
1
1
Order By: Relevance
“…Thus, in the present study, DEX administration may have relieved the depletion of NE engendered by 6 days on the small pedestals. This interpretation is consistent with reports that catecholamine (CA) system function is depressed following REM dep (21) and with reports of NE depletion following the longterm or repeated presentation of unavoidable noxious stimuli (22)(23)(24). Sleep deprivation and its inherent stress, however, have been reported to leave brain NE levels unchanged (20) or to increase NE function (25)(26)(27), so that DEX administration may well have produced the present results by further enhancing the already increased NE.…”
supporting
confidence: 82%
“…Thus, in the present study, DEX administration may have relieved the depletion of NE engendered by 6 days on the small pedestals. This interpretation is consistent with reports that catecholamine (CA) system function is depressed following REM dep (21) and with reports of NE depletion following the longterm or repeated presentation of unavoidable noxious stimuli (22)(23)(24). Sleep deprivation and its inherent stress, however, have been reported to leave brain NE levels unchanged (20) or to increase NE function (25)(26)(27), so that DEX administration may well have produced the present results by further enhancing the already increased NE.…”
supporting
confidence: 82%
“…Although the results obtained when the animals were ex posed to a novel acute stressor suggest that previous chron ic stress did not alter the physiological response to a novel stressor, it has been reported that previous exposure to stress induces a sensitization of the brain noradrenaline res ponse to a subsequent exposure to the same stressor [1,2]. More recently, we have observed that chronic exposure to various stress models enhanced basal and acute stress levels of brain serotoninergic activity.…”
Section: Discussionmentioning
confidence: 71%
“…Ils ont établi que l'hyperactivité neurovégétative observée chez les sujets ayant un TSPT coïncidait avec une hypersensibilité des capteurs de la noradrenaline. Or, Anisman et al (1979) ont trouvé que de faibles chocs électriques n'ayant aucun effet mesurable sur des animaux naïfs, produisaient une diminution importante de la noradrenaline chez des animaux précédemment exposés à des chocs incontrôlables. Ainsi, l'exposition à une situation traumatique (des chocs incontrôlables) induirait cette hypersensibilité des capteurs noradrénergiques, ce qui supporte l'hypothèse de la vulnérabilité.…”
Section: Van Der Koik Et V Hypersensibilité Des Capteurs Noradrénergiunclassified